Value of Fast MVO Identification From Contrast-Enhanced Cine (CE-SSFP) Combined With Myocardial Strain in Predicting Adverse Events in Patients After ST-Elevation Myocardial Infarction - Zhang, Min; Lu, Yuan; Li, Zhi; Shao, Yameng; Chen, Lei; Yang, Yu; Xi, Jianning; Chen, Minglong; Jiang, Tingbo (Frontiers in Cardiovascular Medicine, 2022)
Objectives: Cardiac magnetic resonance imaging (CMR) can be used for a one-step evaluation of myocardial function and pathological features after acute ST-elevation myocardial infarction (STEMI). We aimed to evaluate the value of fast microvascular occlusion (MVO) identification from contrast-enhanced steady-state free precession (CE-SSFP) combined with myocardial strain in predicting major cardiovascular adverse events (MACE) in primary percutaneous coronary intervention (pPCI) STEMI patients. Methods: In total, 237 patients with STEMI who received pPCI and completed CMR scans within the following week were enrolled, MVO identification and the myocardial strain analysis were performed in CE-SSFP images without an additional method. The primary endpoint was the presence of MACE, which is defined as a composite of death, reinfarction, and congestive heart failure (HF). Results: After 13 months of follow-up [IQR: 11–24], 30 patients (14%) developed MACE; the MVO (hazard ratio (HR) was 3.10; 95% confidence interval (CI): 1.14 to 8.99, p = 0.028), and the infarct size (IS) (HR: 1.03; 95% CI: 1.0 to 1.06, p = 0.042) and global longitudinal strain (GLS) (HR: 1.08; 95% CI: 1.01 to 1.17, p = 0.029) were finally associated with MACE. Receiver operating characteristic (ROC) analyses show that the area under the curve (AUC) of GLS was large (0.73 [95% CI, 0.63–0.82], p=0.001), and the best cut-off was −11.8%, with 76.7% sensitivity and 58.9% specificity, which are greater than those of IS (0.70, 95% CI, 0.60–0.81, p < 0.001) and MVO (0.68, 95% CI, 0.58–0.78, p < 0.001). However, combining MVO and GLS resulted in a much greater finding (AUC =0.775, 95% CI: 0.727–0.824, P < 0.001) and better sensitivity and specificity (83.3%, 66.5%). Conclusion: MVO identification from contrast-enhanced cine combined with myocardial strain could be a quick and reliable option for STEMI patients undergoing pPCI; it correlates well with the prognosis of STEMI patients in terms of MACE.